2021
DOI: 10.1111/jocs.16120
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of improvement in atrial functional mitral regurgitation after catheter ablation for atrial fibrillation: Three‐dimensional analysis using multislice computed tomography

Abstract: Background: Several factors associated with atrial functional mitral regurgitation development have been reported; however, geometric changes in the mitral apparatus after catheter ablation for atrial fibrillation have not been sufficiently investigated. This study aimed to clarify what determines improvements in atrial functional mitral regurgitation after sinus rhythm restoration in patients who underwent catheter ablation for atrial fibrillation by using multislice computed tomography.Methods: We analysed v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Catheter ablation of AF patients with severe MR, if planned, should not interfere with the decision and timing of surgical repair. Although recent data suggested that successful CA of AF in patients with moderate MR promotes reverse remodeling on mitral valve apparatus and improves MR, it is not yet demonstrated whether a rhythm-control strategy is superior to a rate-control strategy on clinical outcome in non-severe MR ( Table 2 and Supplementary Table 1 ) ( 58 , 59 ). Therefore, AF management in patients with non-severe primary MR currently follows the general principles for patients with non-valvular AF because no data are available on the benefit of CA in the specific setting of non-severe MR ( 13 , 60 ).…”
Section: Mitral Regurgitationmentioning
confidence: 99%
“…Catheter ablation of AF patients with severe MR, if planned, should not interfere with the decision and timing of surgical repair. Although recent data suggested that successful CA of AF in patients with moderate MR promotes reverse remodeling on mitral valve apparatus and improves MR, it is not yet demonstrated whether a rhythm-control strategy is superior to a rate-control strategy on clinical outcome in non-severe MR ( Table 2 and Supplementary Table 1 ) ( 58 , 59 ). Therefore, AF management in patients with non-severe primary MR currently follows the general principles for patients with non-valvular AF because no data are available on the benefit of CA in the specific setting of non-severe MR ( 13 , 60 ).…”
Section: Mitral Regurgitationmentioning
confidence: 99%